2016
DOI: 10.1002/da.22482
|View full text |Cite
|
Sign up to set email alerts
|

Neural Reactivity to Reward as a Predictor of Cognitive Behavioral Therapy Response in Anxiety and Depression

Abstract: Background Cognitive behavioral therapy (CBT) is a well-established treatment for anxiety and depression; however, response to CBT is heterogeneous across patients and many remain symptomatic after therapy, raising the need to identify prospective predictors for treatment planning. Altered neural processing of reward has been implicated in both depression and anxiety, and improving hedonic capacity is a goal of CBT. However, little is known about how neural response to reward relates to CBT outcomes in depress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
56
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 91 publications
(69 citation statements)
references
References 44 publications
9
56
2
Order By: Relevance
“…Therefore, interventions that are comprised of behavioral activation or distress-based exposures may prove to be the most beneficial treatment for patients who present with reward processing deficits. We also recently demonstrated that a more blunted RewP among adult patients with depression and anxiety predicted greater treatment gains with cognitive behavior therapy (Burkhouse et al, 2016), supporting the notion that this measure can also be useful in identifying those most likely to benefit from intervention. Future research would benefit from examining whether the RewP also demonstrates state-like properties and can be altered through treatment or environmental factors (i.e., stress).…”
Section: Discussionmentioning
confidence: 62%
“…Therefore, interventions that are comprised of behavioral activation or distress-based exposures may prove to be the most beneficial treatment for patients who present with reward processing deficits. We also recently demonstrated that a more blunted RewP among adult patients with depression and anxiety predicted greater treatment gains with cognitive behavior therapy (Burkhouse et al, 2016), supporting the notion that this measure can also be useful in identifying those most likely to benefit from intervention. Future research would benefit from examining whether the RewP also demonstrates state-like properties and can be altered through treatment or environmental factors (i.e., stress).…”
Section: Discussionmentioning
confidence: 62%
“…Combining established risk factors (e.g., parental depression) and affective measures (e.g., blunted reward responses) may further improve efforts to identify youth at greatest risk, while providing a specific target and objective marker of outcome (e.g., increasing reward reactivity). We recently demonstrated that a more blunted RewP among adult patients with depression and anxiety predicted greater treatment gains with cognitive behavior therapy (84), supporting the possibility that affective neuroscience methods can be used to identify those most likely to benefit from intervention.…”
Section: Discussionmentioning
confidence: 95%
“…ERPs can be readily integrated into traditional treatment outcome studies because they can be examined both in relationship to clinical change and as pretreatment predictors of clinical change. If ERPs can predict treatment-related responses, they could then be used to identify those patients who might respond best to treatment (Burkhouse et al 2016) or to help assign patients to specific treatments. ERPs could be used for determining what works best and for whom.…”
Section: Insights and Issuesmentioning
confidence: 99%